EKONOMI POLITIK DALAM PEMBANGUNAN INDUSTRIALISASI GLOBAL - Ely Steven Ingratubun; Wihalminus Sombolayuk (SIMAK, 2018)
The dynamics of globalization and liberalization of the world economy are moving so fast, encouraging increased openness of economic relations between nations. Through various trade agreements, such as APEC, AFTA and CAFTA, competition is increasing. According to the World Economic Forum on global competitiveness, Indonesia was ranked 69th (among 177 countries studied) in 2004 and fell to 74th in 2005 .. The development of industrialization in the global economy is a step strategy in response to economical globalization. The involvement of Indonesia in the global economic cooperation has increased its national commitment, both in undergoing economic liberalization and in developing its national economic competitiveness. This research illustrates Indonesia's political challenges in responding to the dynamic changes of the global economy. So this research is in the form of a literature review of the literature on political economy about the development of global industries as one of the central economies of a country, especially Indonesia in order to stabilize future economic fundamentals. This study aims to find out and explore the role of political economy in the development of global industries in each country, both developing and developed countries and this research to determine the extent to which the role of global industrialization affects the economy of a country in the future.